The Influences of Visceral Fat Area on the Sites of Esophageal Mucosal Breaks in Subjects with Gastroesophageal Reflux Diseases - Ji Hyung Nam; Eirie Cho; Jeung Sook Kim; Eun-Cheol Park; Jae Hak Kim (Gastroenterology Research and Practice)
Background. Central obesity is suggested as a risk factor for gastroesophageal reflux diseases. The aim of this study was to evaluate the influences of a visceral fat area on the site of mucosal breaks in the esophagogastric junction (EGJ). Methods. Subjects who underwent abdomen-computerized tomography and esophagogastroduodenoscopy for screening on the same day were evaluated between 2007 and 2016. We enrolled 178 subjects who had erosive esophagitis (LA classifications A-D). Abdominal obesity was evaluated by measuring visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), VAT-to-SAT ratio, total adipose tissue (TAT), body mass index (BMI), and waist circumference (WC). Results. The lesser curvature (LC) of EGJ was the most frequent site of mucosal breaks (104 cases, 58.4%). BMI, WC, VAT, the VAT-to-SAT ratio, and TAT were higher in the LC group. In multivariate analysis, higher VAT (odds ratio (OR) 2.90, 95% confidence interval (CI) 1.18 to 7.13, 3rd vs. 1st quartile, P=0.021; OR 3.63, 95% CI 1.44 to 9.10, 4th vs. 1st quartile, P=0.006) and the VAT/SAT ratio (OR 2.91, 95% CI 1.11 to 7.61, 3rd vs. 1st quartile, P=0.03; OR 3.02, 95% CI 1.17 to 7.83, 4th vs. 1st quartile, P=0.023) were significantly associated with mucosal breaks in the LC group. However, BMI, WC, and TAT were not significant in the multivariate analysis. Conclusion. The VAT and the VAT/SAT ratio were significantly associated with the mucosal breaks in the LC of EGJ. Visceral obesity could influence the location of the mucosal breaks on EGJ.